Social ontology, normativity and law - García Godínez, Miguel Ángel; Mellin, Rachael; Tuomela, Raimo (De Gruyter, 2020)
This volume contains the proceedings of the Social Ontology, Normativity, and Philosophy of Law conference, which took place on May 30-31, 2019 at the University of Glasgow. At the invitation of the Social Ontology Research Group, a panel of prominent scholars shed light on a range of key topics within social ontology, normativity, and philosophy of law from an interdisciplinary perspective.